Conceptual design of two adaptive mechanisms to irregular surfaces for a street sweeping brush - Mamani, Rosendo D. Velez; Bermudez, Gabriel; Rodrίguez, José Canazas; Vidal, Yuri L. Silva; Guzmán, Paulo Y. J. Silva (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Road litter pollutes significantly affect people’s lives and vehicle movement, a situation exacerbated by irregular urban surfaces. Although Actually is existing research on the design of sweeping robots, optimizations need to be adapted to the specific context of each environment. Given the irregular nature of road surfaces, this paper suggests designing two electromechanical mechanisms capable of adapting to uneven terrains, ensuring that the brush remains in contact with the ground. To achieve this, two 3D models were developed using the SolidWorks ComputerAided Engineering (CAE) software, incorporating design criteria focusing on adaptability, resistance, and effective coupling between the systems of the mechanisms. Subsequently, these models were compared through dynamic analysis dynamic analysis carried out in the SolidWorks Motion Studies module on a proposed irregular terrain that simulates real-world conditions. The simulation was carried out at various displacement speeds to examine the existing contact forces in critical components, followed by a dynamic stress analysis at points of higher contact force. The results suggest that Model 2 is more effective in dealing with terrain irregularities. However, Model 1 is capable of reaching greater depths and heights. Furthermore, the vertical oscillating axis of Model 1 experiences reduced contact forces in comparison to Model 2. It has been shown that neither Model encounters stress concentration at speeds below 0.6.